Assessment of users’ satisfaction in physiotherapy service - Oliveira, Franciele Santos de; Fernandes, Aline Braga G. Silveira; Lins, Caio Alano de Almeida; Silva, Rodrigo Scattone da; Lima, Núbia Maria Freire Vieira; Souza, Marcelo Cardoso de (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Satisfaction of the health service user involves multiple factors and dimensions beyond the eminently clinical setting and is inserted in the process of evaluation of health services. It is known that the patient as a source of opinions and suggestions, assists in the process of improving the services offered. Objective: The aim of this study was to evaluate the satisfaction of patients followed in Physical Therapy. Method: It is a cross-sectional descriptive observational research with quantitative and qualitative approach. Two questionnaires (MedRisk and instrument for measuring patient satisfaction with physical therapy in the public health system) were applied in 100 patients. Dimensions were evaluated related to therapist/patient relationship, consultation marking, physical environment, access physical structure and global items. Results: The sample was characterized by the predominance of female users, school graduated and with family income between one and three minimum wages. Most were answered in orthopedics, neurology and rheumatology. 45 objective questions were applied and 42 prevailed at the maximum score. Conclusion: Through the analysis, it was found that the patients mostly were satisfied with the service offered.